2020
DOI: 10.1111/afe.12422
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of the cerambycid beetlesTetropium gabrieli,T. castaneumandT. fuscumto pheromones and host tree volatiles

Abstract: Tetropium gabrieli is native to the European Alps where it breeds in European larch and may be an important pest during drought periods by killing trees. It has spread to larch plantations in several European countries including Sweden. In trapping studies conducted in Sweden, we tested whether T. gabrieli was attracted to E‐fuscumol, E,Z‐fuscumol, E,Z‐fuscumol acetate and the host volatile combination of α‐pinene plus ethanol. We also compared its response with those of the native congeners, T. fuscum and T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The brown spruce longhorn beetle, Tetropium fuscum Fabricius (Coleoptera: Cerambycidae), is a harmful forest pest native to Europe where it attacks weakened Norway spruce, Picea abies L. [ 1 , 2 ]. It first became invasive to North America around 1990 [ 3 , 4 ], where it was infecting and killing healthy native spruces, such as red spruce ( Picea rubens Sargent), white spruce ( Picea glauca Moench), blue spruce ( Picea pungens Engelm), and black spruce ( Picea mariana Miller) [ 5 , 6 ]. Due to its subcortical feeding habits [ 7 , 8 ], systemic insecticides and heating are not very effective and practical [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The brown spruce longhorn beetle, Tetropium fuscum Fabricius (Coleoptera: Cerambycidae), is a harmful forest pest native to Europe where it attacks weakened Norway spruce, Picea abies L. [ 1 , 2 ]. It first became invasive to North America around 1990 [ 3 , 4 ], where it was infecting and killing healthy native spruces, such as red spruce ( Picea rubens Sargent), white spruce ( Picea glauca Moench), blue spruce ( Picea pungens Engelm), and black spruce ( Picea mariana Miller) [ 5 , 6 ]. Due to its subcortical feeding habits [ 7 , 8 ], systemic insecticides and heating are not very effective and practical [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that climate change and the increase in prolonged droughts were among the main predisposing factors for the following attacks by T. gabrieli on Larix spp. [8,41]. Thus, a similar situation can be expected in the near future in Lithuania.…”
Section: Life Cyclementioning
confidence: 56%
“…Among the destructive Tetropium species, T. gabrieli (Weise, 1905) was reported being native to the Alps in central Europe where it breeds in European larch (Larix decidua Mill.) [7,8]. In Lithuania, it was not observed previously, but listed in the catalogue of Lithuanian beetles as a probable for the local fauna [9].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations